THE EFFECT OF Sauropus androgynus LEAF EXTRACT ON PERFORMANCE, EGG QUALITY AND CHEMICAL COMPOSITION OF EGGS - Santoso, U.; Fenita, Y. (Journal of the Indonesian Tropical Animal Agriculture, 2016)
The purpose of this research was to produce the enriched eggs, but low in cholesterol content. Forty eight layer chickens aged 72 weeks (strain Dekalb Warren) were distributed into six treatment groups. One group of laying hens was fed diets without Sauropus androgynusleaf extract (SALE) as the control, and another five groups were fed diet supplemented to 9 g SALE, 18 g SALE, 27 g SALE, 36 g SALE, and 45 g SALE/kg diet, respectively. Completely randomized design was used in the present study.The experimental results showed that SALE supplementation had no effect on egg production, feed intake, feed conversion ratio, egg weight, yolk weight, albumen weight, shell egg, egg index, eggshell thickness, and yolk index (P>0.05), but significantly affected Haugh Unit, albumen index, yolk color, egg odor, egg taste, and yolk color (P<0.05). The protein, fat, calsium, phosphor, kaliumand iron contents of eggs  did not change (P>0.05), but the cholesterol content of egg was significantly reduced (P<0.05). In conclusion, the supplementation of SALE did not enhance performance, but it improve egg quality and its chemical composition.